2020
DOI: 10.1093/rheumatology/keaa784
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of rheumatoid arthritis among patients with endometriosis: a nationwide population-based cohort study

Abstract: Objectives Autoimmunity may play a role in endometriosis. The association between endometriosis and RA remains unknown. This study was conducted to identify any evidence for this relationship. Methods This 13-year, nationwide, population-based, retrospective cohort study analysed the risk of RA in a cohort of individuals with endometriosis. We investigated the incidence of RA among patients with endometriosis using data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…(2021), demonstrated an increased risk of SLE (adjusted HR= 2.37, 95% CI=1.35-4.14) compared to the non-endometriosis patients ( 27 ). In addition, another study suggested that women with endometriosis were significantly associated with rheumatoid arthritis ( 20 ). An immunological and inflammatory etiology has been speculated, as indicated by increased concentrations of activated macrophages, cytokines, T cells, and B cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2021), demonstrated an increased risk of SLE (adjusted HR= 2.37, 95% CI=1.35-4.14) compared to the non-endometriosis patients ( 27 ). In addition, another study suggested that women with endometriosis were significantly associated with rheumatoid arthritis ( 20 ). An immunological and inflammatory etiology has been speculated, as indicated by increased concentrations of activated macrophages, cytokines, T cells, and B cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggest that women with endometriosis may have a hormonal imbalance and be prone to other immune surveillance-related imbalances such as suppressed cell-mediated immunity (high T, B, and NK cell counts, but lessened activity) and increased antibody-mediated immune response (high serum levels of immunoglobulin IgA, IgG, IgM, and anti-endometrial antibodies) ( 30 ). In addition, inflammatory cytokine concentrations like IL-1, IL-6, and TNF-α were elevated among endometriosis patients ( 20 ). Patients with endometriosis also present with other chronic inflammatory diseases, chronic inflammation, and increased oxidative stress ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have discussed, the IL-23/Th17 axis is dysregulated in EMS, as well as various other chronic inflammatory diseases, including psoriasis, inflammatory bowel disease, rheumatoid arthritis, and multiple sclerosis [185,188,200,203,204]. The clinical presentation of these diseases alongside EMS has been extensively discussed [165,202,[205][206][207][208]. Here, we will focus on the current gaps in the literature, particularly on the possible pathophysiological pathways shared between EMS and its comorbidities in order to aid in the discovery of novel therapeutic targets.…”
Section: Immune-centered Comorbities May Share Common Pathological Me...mentioning
confidence: 96%
“…Another case-control study demonstrated an increasing number of immune-mediated conditions and co-occurring endometriosis [5]. A nationwide population-based study showed an increased risk of RA in patients with endometriosis during more than 10-year follow-up [6]. A population-based, retrospective cohort study from Taiwan including endometriosis (n = 16,758) and non-endometriosis (n = 16,758) women showed a significantly higher incidence rate in women with endometriosis (0.3 vs. 0.1 per 1,000 person-years) and hazard ratio (HR) for SLE [adjusted HR (aHR), 2.37; 95% confidence interval (CI) 1.35-4.14] as compared to the non-endometriosis group [7].…”
Section: Endometriosis and Autoimmune Diseasesmentioning
confidence: 99%